Pengaruh Latihan Menggunakan Alat Bantu Tali Pinggang Terhadap Peningkatan Passing Sepak Bola Universitas Muhammadiyah Palopo - Mulyakin, Dodi; Jalil, Rasyidah; Riswanto, Andi Heri (Universitas Hamzanwadi, 2025)
This study aims to determine the effect of training using waist strap aids on improving passing ability in soccer athletes. This study uses quantitative methods with a pre-experimental design in the form of one-group pretest and posttest. The population in this study was 15 athletes. A total of 15 soccer athletes from Universitas Muhammadiyah Palopo were sampled in this study. Data were collected through passing tests before and after being given treatment in the form of training using a waist strap tool. The results showed a significant increase in passing ability after the treatment was given. Based on statistical analysis, the posttest results showed that 60% of athletes were in the excellent category, compared to 0% in the pretest. After being given treatment using the help of a waist strap. There were 9 (60%) athletes in the Excellent category, and 6 (40%) athletes in the good category, 0 (0%) athletes in the fair category, 0 (0%) athletes in the low category. This study contributes to the understanding of the effectiveness of training using a waist strap tool in improving technical skills in football, and can be the basis for coaches to develop more effective training programs.